Forms of power and energies of change in the works of Chinua Acbebe, Bessie Head and Dambudzo Marechera - Gagiano, Annie,1947- (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- University of Stellenbosch, 1998.